The Regressive Demands of Demand-Driven Development - Baird, Sarah; McIntosh, Craig; Özler, Berk (Elsevier, 2013)
Despite their explicit focus on reaching the poor, many community driven development (CDD) initiatives are only partially successful in targeting spending towards them. This paper examines Tanzania's flagship CDD program and provides new evidence on the mechanisms by which the demand-driven components of the program may undermine the goal of pro-poor funding allocations. We exploit two data sources for the analysis: a census of wards for mainland Tanzania and a census of households in 100 program villages. These data paint a consistent picture at both levels: wealth, education, access to media, and political engagement are positively correlated with the likelihood to apply for the program at the national level, and to be aware of it at the local level. Centrally dictated features of the program – namely predetermined funding allocations to districts and eligibility rules – combine with the decentralized selection process within districts to counteract this initially regressive application pattern and produce a program that is, like many other CDD programs, only mildly pro-poor. Our results suggest that sensitization and outreach prior to the application process will be a critical dimension in making CDD programs more progressive.